Ras and Rab interactor 3 as a prognostic biomarker and its impact on immune cell infiltration in cancer - Xin Xu; Ningfeng Zhou; Shasha Zhang; Tingxin Cheng; Jun Ren; Dian Yang; Ying Liu; Shiyan Wang; Aijun Sun; Fengze Cai (Scientific Reports)
Abstract RIN3, a member of the RIN protein family, plays a pivotal role in disease progression by modulating Rab5 activity and influencing cell signaling pathways, which in turn affect tumor proliferation and migration. Our study systematically examined RIN3 expression in various tumor types using data from TCGA, GTEx, and single-cell RNA sequencing of 77 tumor types in the TISCH database, aiming to clarify its potential role in cancer. We evaluated the association between RIN3 levels and patient survival via univariate Cox regression and analyzed its correlation with immune cell infiltration using TIMER2.0. Additionally, GSEA and GSVA were employed to explore the involvement of RIN3 in immune responses and metabolic processes, while molecular docking and bioinformatics approaches predicted its interactions with anticancer drugs. Functional assays in breast cancer models confirmed that downregulation of RIN3 significantly inhibited cell proliferation and migration. Our results revealed considerable variations in RIN3 expression across tumors, an inverse relationship with CNVs and DNA methylation, and a significant correlation with immunotherapy biomarkers. These findings suggest RIN3 as a promising biomarker and therapeutic target, particularly for BRCA-mutated cancers, and may guide the development of novel anticancer strategies.